2020
DOI: 10.5812/asjsm.83927
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Exercise Therapy and Dry Needling on Wrist Range of Motion, Pinch and Grip Force in Carpal Tunnel Syndrome: A Randomized Clinical Trial

Abstract: Background: Carpal tunnel syndrome (CTS) is the most prevalent form of peripheral neuropathy. There are various treatments for carpal tunnel. Objectives: In this study, we evaluated the effect of electroacupuncture and exercise on pinch and grip strength and wrist range of motion in patients with mild to moderate CTS. Methods: Sixty patients with carpal tunnel syndrome were evaluated in this study, only five of whom were male. In this study, patients were divided into three groups. The control group consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…However, exercise therapy had the greatest effect on increasing the range of motion, whereas there was no study evaluating the effectiveness of acupuncture on movement activities in the treatment of CTS. 18 Edwards and Knowles determined that superficial DN plus active stretching was considerably more effective in suppressing the cause factors as compared to active stretching only. Pain threshold measurement literature suggests that superficial DN is an effective approach for deactivating TrP, as the TrPs require deactivation before stretching, with the likely relaxation of tight muscle bands.…”
Section: Results Discussionmentioning
confidence: 99%
“…However, exercise therapy had the greatest effect on increasing the range of motion, whereas there was no study evaluating the effectiveness of acupuncture on movement activities in the treatment of CTS. 18 Edwards and Knowles determined that superficial DN plus active stretching was considerably more effective in suppressing the cause factors as compared to active stretching only. Pain threshold measurement literature suggests that superficial DN is an effective approach for deactivating TrP, as the TrPs require deactivation before stretching, with the likely relaxation of tight muscle bands.…”
Section: Results Discussionmentioning
confidence: 99%
“…Study reported that low-intensity electroacupuncture was antiinflammatory and relieved pain by driving the vagal-adrenal anti-inflammatory axis and by inducing vagal activation of aromatic L-amino acid decarboxylase (42,43). Recently, some studies (34,35) have reported that electroacupuncture provided better clinical outcomes than other treatments. However, no guideline or consensus was established regarding which type of treatment was preferable to improve clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…57 Acupuncture therapy can be considered as an alternative management for patients who can't go through for early decompression surgery. 58 Hidayati HB, et al carpal tunnel syndrome www.apicareonline.com 401 Open access attribute (CC BY-NC 4.0)…”
Section: Pharmacological Managementmentioning
confidence: 99%